Advanced trajectory generator for two carts with RGB-D sensor on circular rail - Panduro, Ramon (2019)
This paper presents a motorised circular rail that generates the motion of two carts with an RGB-D sensor each. The objective of both carts' trajectory generation is to track a person's physical rehabilitation exercises from two points of view and his/her emotional state from one of these viewpoints. The person is moving freely his/her position and posture within the circle drawn by the motorised rail. More specifically, this paper describes the calculation of trajectories for safe motion of the two carts on the motorised circular rail in detail. Lastly, a study case is offered to show the performance of the described control algorithms for trajectory generation.